Late Quaternary megafans, fans and fluvio-aeolian interactions in the Bolivian Chaco, Tropical South America - Latrubesse, Edgardo M.; Stevaux, Jose C.; Cremon, Edipo H.; May, Jan-Hendrik; Tatumi, Sonia H. [UNESP]; Hurtado, Martín A.; Bezada, Maximiliano; Argollo, Jaime B. (Elsevier, 2012)
The Chaco is a huge plain and a main biogeographic biome of South America dominated by subtropical semi-deciduous vegetation that spreads on the Andes footslope on more than 800,000km 2 through Bolivia, Argentina and Paraguay. The climate is tropical wet-dry and the South American Summer Monsoon (SASM) leads to intensive convective rainfall during the summer season. Some of the world's largest river-fans such as the Parapeti and Grande rivers megafans developed in the Bolivian Chaco. Our research was based on morpho-sedimentary information and sustained by 25 OSL dating of fluvial and aeolian sediments. We demonstrate that these megafans are bigger than previously postulated by some authors. Morphostratigraphic analysis, geochronological data and regional correlations suggest that the Chaco megafans and large piedmont fans were generated and reached maximum development during the middle pleniglacial and early pleniglacial (ca. 60 to 28ka) because of the presence of colder and more seasonal conditions (dry-wet intense contrasting seasons) than those existing today in the Amazon and the Bolivian plains. We suggest that a main mechanism triggering the megafan development was the presence of an intense monsoonal effect on the Eastern flank of the Andes that enhanced rainfall by orographic excitation during MIS 3 and the early part of MIS 2 that produced an increase in discharge and sediment supply. Concomitantly to fluvial processes the deflation of fluvial belts occurred and big sand dune fields developed by winds blowing out from North to South following the same pattern the South American lower level jet follows presently. Maximum aridity was reached during MIS 2 with the deposition of loess deposits on the piedmont areas and megafan surfaces, the continuous generation of aeolian dunes and a remarkable decrease in the fluvial activity. Cold air mass related to the polar advection (friagens or surazos) probably affected the area with more intensity and frequency. The Lateglacial was also arid but probably less extreme than the LGM. During a good part of the Holocene the climatic conditions were still arid to semiarid but became more similar to the present sub-humid climate since ~1.5ka. During the Holocene, the megafans and aeolian systems didn't reach Late Pleistocene size and level of activity. © 2012 Elsevier B.V.
Keywords: Chaco; Fluvio-aeolian; Megafans; Paleogeography; Quaternary; Tropical South America